The oral microbiome of patients with ischemic stroke predicts their severity and prognosis - Sun, Wenbo; Huang, Shengwen; Yang, Xiaoli; Luo, Yufan; Liu, Luqiong; Wu, Danhong (Frontiers in Immunology, 2023)
Background and Objectives: Stroke is a common group of cerebrovascular diseases that can lead to brain damage or death. Several studies have shown a close link between oral health and stroke. However, the oral microbiome profiling of ischemic stroke and its potential clinical implication is unclear. This study aimed to describe the oral microbiota composition of IS, the high-risk of IS, and healthy individuals and profile the relationship between microbiota and IS prognosis. Methods: This observational study recruited three groups: ischemic stroke (IS), high-risk ischemic stroke (HRIS), and healthy control individuals (HC). Clinical data and saliva were collected from participants. The Modified Rankin scale (mRs) score after 90 days was used to assess the prognosis of stroke. Extracted DNA from saliva and performed 16S rRNA gene amplicon sequencing. Sequence data were analyzed mainly using QIIME2 and R packages to evaluate the association between the oral microbiome and stroke. Results: A total of 146 subjects were enrolled in this study according to the inclusion criteria. Compared to HC, HRIS and IS demonstrated a progressive increase trend in Chao1 and Observed species richness, as well as Shannon and Simpson diversity. Based on PERMANOVA analysis, the data indicate great variation in the saliva microbiota composition between HC and HRIS (F = 2.40, P < 0.001), HC and IS (F = 5.07, P < 0.001), and HRIS and IS (F = 2.79, P < 0.001). The relative abundance of g_Streptococcus, g_Prevotella, g_Veillonella, g_Fusobacterium, and g_Treponema was higher in HRIS and IS compared to HC. Furthermore, we constructed the predictive model by differential genera to effectively distinguish IS patients with poor 90-day prognoses from IS patients with good. (AUC=79.7%, 95%CI: 64.41%-94.97%; p <0.01) Discussion: In summary, the oral salivary microbiome of HRIS and IS subjects have a higher diversity, and the differential bacteria have some predictive value for the severity and prognosis of IS. Oral microbiota may be used as potential biomarkers in IS patients.